(untitled) (Bangladesh Medical Journal, 2014)
Gestational trophoblastic tumour/disease (GTT/GTD) is unique it cancer biology in that they result from aberrations of either a normal or an abnormal pregnancy. The most common antecedent pregnancy event to GTT is a complete or partial hydatidiform mole (HM). However, persistent trophoblastic disease or choriocarcinoma can follow a complete hydatidiform mole with an incident of approximately 8%, and after a partial hydatidiform mole with an incidence of approximately 0.5%. The exact proportion of cases of hydatidiform mole transforming to choriocarcinoma cannot be clearly estimated, approximately 3% to 5% of cases of complete hydatidiform mole. 1-3 Therefore, all patients with GTT need to be monitored so that the small proportion of persistent mole or choriocarcinoma can receive prompt treatment and elimination of their’ disease. The recommendation stands as strict avoidance of pregnancy for at least one year after treatment of molar pregnancy or low risk non-metastatic gestational trophoblastic tumour. Pregnancy during this period of surveillance interferes with the sequential monitoring of abnormal trophoblastic activity by serum beta-human chorionic gonadotrophin levels and relapses become difficult to detect. The effect of single agent or combination chemotherapy on the totipotent oocytes usually wavers away during the recommended period of contraception. But in cases of pregnancy during the period of surveillance certain factors have been found to be associated with increased risk of relapse and teratogenic effects of the offspring. High risk/score (according to the FIGO scoring system ) and advanced stage Gestational trophoblastic tumour (GTT), short interval between pregnancy and remission from combination chemotherapy, poor compliance during the antenatal follow-up are linked with detrimental maternal and foetal outcome. Here we report a case of successful pregnancy outcome in a patient who conceived within 3 months of remission from choriocarcinoma treated by methotrexate as evidenced by 2 consecutive negative ?-human chorionic gonadotropin (?-hCG) values. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18671 Bangladesh Medical Journal 2011 Vol.40(3):29-32